Internal Talent Mobility and Career Development: A Bibliometric Review - Judijanto, Loso; Amalia, Fisy (Westscience Press, 2025)
This study presents a bibliometric review of the academic literature on internal talent mobility and career development, aiming to map the intellectual structure, thematic evolution, and collaborative networks within the field. Utilizing data from the Scopus database and analyzed through VOSviewer, the study identifies key trends in author influence, keyword co-occurrence, temporal distribution, and country collaboration. Findings indicate that core topics such as career development, talent management, succession planning, and leadership development form the backbone of the research landscape, while emerging themes like internal consistency, career mobility, and strategic investments signal new directions. The United States leads in scholarly output and international collaboration, with growing contributions from China, Canada, and Germany. Author co-citation analysis reveals strong theoretical foundations, yet the literature remains fragmented across disciplines. The study highlights critical gaps in equity, technology integration, and cross-cultural research, offering a foundation for future exploration. This bibliometric review contributes to the strategic advancement of theory and practice in managing internal talent and fostering sustainable career growth.